Метод визначення спроможності "обмежувача перенапруг нелінійного" поглинати енергію без втрати теплового балансу - Шевченко, С.Ю. (Електротехніка і електромеханіка, 2015)
На основе экспериментально полученных вольтамперных характеристик варисторов определено напряжение, при
котором ограничитель перенапряжений нелинейный (ОПН) начинает проводить активный ток, что позволило получить уточненную математическую модель для расчета энергии, которая действует на ОПН и разработать метод
оценки способности ОПН поддерживать тепловой баланс на протяжении всего срока эксплуатации. На основі експериментально отриманих вольтамперних характеристик варисторів визначена напруга при якій обмежувач перенапруг нелінійний (ОПН) починає проводити активний струм, що дозволило отримати уточнену математичну модель для розрахунку енергії, що впливає на ОПН та розробити метод оцінювання спроможності ОПН
підтримувати тепловий баланс на протязі всього строку експлуатації. Purpose.The aim of this study is to obtain a method for determining the capacity surge arrester nonlinear absorb energy
without breaking the heat balance in modes of long-term application of operating voltage, which allows for analysis of their
work in terms of violations as electricity. Methodology. For
values of the energy passing through the arrester must be able
to determine the current value for the voltage value in the area
of leakage current-voltage characteristics. We have carried out
calculations of the energy passing everywhere arrester for certain periods of time based on the current-voltage characteristics
obtained experimentally. Analysis of the experimental currentvoltage characteristics of resistors and literature led to the important conclusion that the dielectric properties of the ceramic
varistor affect the value of active power losses in the arrester
only when the active component of the leakage current is very
small. This is confirmed by the characteristics of different
classes of varistor voltage. This property of varistors and surge
arresters shows the need to consider how the dielectric and
conductive properties of the varistor ceramics in the analysis of
work in the area of the arrester leakage current-voltage characteristic. These results demonstrate the need to clarify the mathematical model and the method for determining the energy dissipates in the area of the arrester leakage current CVC with their
account. Results. The study, an improved mathematical model
for calculating energy affects surge arrester during its working
life. The study obtained the method, of evaluation capacity surge
arrester, maintains heat balance throughout working life. Based
on experimentally obtained current-voltage characteristic of the
varistors is defined voltage at which surge arrester starts conducting active current. This allowed to receive specified mathematical model for calculating energy affects surge arrester and
develop a method of evaluation capacity surge arrester maintain
heat balance throughout working life.